PENERAPAN REHABILITASI JANTUNG FASE 1 PADA PASIEN SINDROMA KORONER AKUT (SKA) DI RUMAH SAKIT JANTUNG DAN PEMBULUH DARAH HARAPAN KITA JAKARTA - Ridho Kunto Prabowo (SEKOLAH TINGGI ILMU KESEHATAN (STIKes) INDRAMAYU, 2019)
Cardiac rehabilitation is all actions taken to optimally improve physical, mental and social functioning to restore functional capacity in patients with life-threatening acute coronary or post-invasive patients. Phase I cardiac rehabilitation is an immediate initiation to carry out cardiac rehabilitation in the acute phase. This study aims to identify the application of phase 1 cardiac rehabilitation in ACS patients. Research using quantitative design with descriptive approach. The research sample consisted of 12 respondents using purposive sampling technique. The results of phase 1 to level 1 to 3 day 5 cardiac rehabilitation studies in patients with ACS obtained Chest Pain, Dyspnea and ECG images whose values ​​were constant or the same for all respondents both at the beginning, exercise and end. It can be concluded that during phase 1 level 1 heart rehabilitation to level 3 days 5 there were no changes in Chest Pain, Dyspnea and ECG in SKA patients. While the difference in heart rate and blood pressure values ​​statistically showed significant, but clinically not significant. Suggestion phase 1 cardiac rehabilitation is a safe action and can be done independently by nurses and therefore must be applied to ACS patients. Keywords: Phase 1 Cardiac Rehabilitation, Acute Coronary Syndrome